TESTING DETERGENT PUMP CONTROL IN RESIDENTIAL WASHING MACHINES WITH FUZZY CONTROL METHOD - Sangadi Pratomo, Yohanes Fredhi; Indah, Nur (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2024)
Currently laundry service providers are mushrooming, this is because most people are busy with office work and activities, while homework cannot be ruled out, for example washing clothes. Cleanliness of clothes is an absolute thing that must be achieved. The thing that most influences the cleanliness of laundry results is the right amount of water and the appropriate detergent capacity. If the detergent capacity is adjusted to the water capacity and number of clothes, maximum results will be obtained. To overcome this, a detergent pump with fuzzy logic was made for the control system. Fuzzy logic provides a limit on the detergent volume adjusted for the input of water volume and the capacity of the clothes to be washed. For input data taken using a flow meter sensor to measure the volume of water used and a potentiometer to provide input weight of clothes to be washed. From the input data, the fuzzy logic method will produce detergent volume according to needs, so there is no excess detergent volume that can cause damage to clothes and reduce the live time of the washing machine. With a pump using a peristaltic pump, the resulting detergent volume is expected to be more stable. With the results of three volume variable experiments namely 20ml, 40ml, and 60ml obtained a maximum error data of 4.01% of the expected volume, the deviation of the desired detergent volume is not too much, so it is expected to reduce excess expenditure on the use of detergent. As for the fuzzy logic method that is applied can provide output results that are adjusted to changes in clothing weight between 5kg - 15kg and changes in the volume of water used between 37L - 56L so that it is expected to provide optimal results during the washing process. The system is designed using a maximum voltage of 12V DC and 3A current making this device low-power only 36 watts. This tool does not consume too much electricity.